Cross-cultural psychological studies in educational settings on Asia: Bibliometric analysis and narrative study - Alim Panggih Raharjo; Khurun In Amaliyah; Siti Nur Azizah; Reni Ferida; Nafiatul Khasanah (University of Merdeka Malang, 2024)
ABSTRACTThe culture of Asian societies that are different from the West can influence different approaches to the educational process. Understanding the differences in cross-cultural psychology in Asia and the West can help teachers and curriculum designers provide appropriate learning techniques and strategies for multicultural students. This study aims to find out 1) Cross-cultural psychology research trends in educational settings, 2) Mapping the cross-cultural psychology studies in educational settings, and 3) Explaining cross-cultural psychology studies in educational settings in Asia. The methods used are bibliometric analysis (VOSViewer) and narrative studies. The result is that research trends are less desirable or researched and research topics related to cultural competency, attitude, comparative study, student-teacher relationship, and adaptation.ABSTRACTBudaya masyarakat Asia yang berbeda dengan wilayah Barat dapat memengaruhi perbedaan pendekatan-pendekatan dalam proses pendidikan. Memahami perbedaan psikologi antarbudaya di Asia dan wilayah Barat dapat membantu guru dan perancang kurikulum untuk memberikan teknik dan strategi pembelajaran yang tepat bagi siswa yang multikultur. Studi ini bertujuan untuk mencari tahu 1) Trend penelitian psikologi lintas budaya dalam setting pendidikan, 2) Memetakan studi-studi psikologi lintas budaya dalam setting pendidikan, dan 3) Menjelaskan kajian psikologi lintas budaya dalam setting pendidikan di Asia. Metode yang digunakan yaitu analisis bibliometrik (VOSViewer) dan studi naratif. Hasilnya bahwa trend penelitian kurang diminati atau diteliti dan topik penelitian berkaitan dengan cultural competency, attitude, comparative study, student-teacher relationship, dan adaptation.